The Relationship Between Zinc and Calcium Intake and Primary Dysmenorrhea in Adolescent Girls at SMA Negeri 1 Rantau Seselan - Nila Reswari Haryana; Nazrina Askila (Universitas Negeri Semarang, 2025)
Painful cramps in the lower abdomen characterize primary dysmenorrhea. The cramps or pain you feel can be reduced by consuming adequate zinc and calcium. This study aimed to determine the relationship between zinc and calcium intake and primary dysmenorrhea in adolescent girls at SMA Negeri 1 Rantau Selatan. This research was conducted in July 2024 at SMA Negeri 1 Rantau Selatan. The design of this research was cross-sectional; the study sample consisted of 44 participants selected through purposive sampling. The data collection technique involves completing the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) and Numerical Rating Scale (NRS) independently, under the supervision and direction of researchers. The results of this study showed that the majority of respondents had insufficient zinc intake (63.6%) and sufficient calcium intake (65.9%), and 50% experienced primary dysmenorrhea. Data analysis was conducted using the chi-square test and logistic regression analysis. Based on the analysis results, a significant relationship (p < 0.05) was found between zinc and calcium intake and primary dysmenorrhea. Meanwhile, young women who consume less calcium have a 14,566 times higher risk of experiencing dysmenorrhea, while those who consume less zinc have a risk of experiencing dysmenorrhea 11,790 times. A sufficient intake of zinc and calcium can help reduce primary dysmenorrhea by regulating uterine muscle contractions.